Study of biochemical and nutritional indicators in severe acute malnutrition: A prospective observational study - Lakshmi, M; Sreenivas, S K; Pavitra, N A; Nath, Sudheendra (Indian Journal of Child Health, 2016)
Background: Malnutrition in children is widely prevalent in developing countries including India. More than 33% of the deaths in 0-5 years are associated with malnutrition. Children with severe acute malnutrition (SAM) are in danger of death from hypoglycemia, hypothermia, fluid overload, electrolyte mismanagement, and undetected infections. Hence, biochemical and nutritional indicators in these children are important for management. Objectives: To study the biochemical and nutritional indicators in children with SAM. Methods: This hospital based prospective study was conducted on children aged 6-59 months admitted at Nutrition Rehabilitation Center attached to a tertiary care teaching institution. 100 consecutive SAM children admitted during 2013-2015 were studied. Children were tested for biochemical and nutritional status like complete blood picture with peripheral smear, liver function tests, renal function tests, serum electrolytes, calcium, phosphorus, and alkaline phosphatase. Results: A total of 100 cases were included, of these 57 were male and female were 43. Mean age of presentation was 18.45±2.37 months. A lack of exclusive breastfeeding was seen in 67% of these children and in 78% children complimentary feeds were initiated either early or later than 6 months. Hypoglycemia was seen in 15% cases, hypokalemia in 22%, and hypocalcemia in 35% of cases. Hyponatremia was seen in 14% and hypernatremia in 19% of the children. The most common type of anemia was microcytic hypochromic type (55%). Conclusion: The observations in this study confirm a significant association between SAM and faulty feeding and early introduction of complementary feeds. It was observed that these children have significant alterations in nutritional indicators at admission.